Analysis of Microbial Community Structure in Traditional and Automated Moutai-Flavor Daqu. (3rd April 2019) - Wang, Xiao-Dan; Qiu, Shu-Yi; Li, Pei; Ban, Shi-Dong
Abstract: The objective of this study was to analyze microbial community structure of traditional and automated Daqu. Bacteria, molds, and yeasts of two Moutai-flavor Daqu samples that were isolated and screened using a culture-dependent method and microbial community structure using a culture-independent method (high-throughput sequencing). Results showed that 15 and 78 microbial genera were identified using culture-dependent and culture-independent methods in automated Moutai-flavor Daqu (GT01) and traditional Moutai-flavor Daqu (GT02) samples, respectively. In particular, Bacillus, Aspergillus, and Saccharomycopsis were demonstrated to be the common dominant bacterial, fungi, and yeast genera in GT01 and GT02 samples, respectively. In addition, qPCR (a culture-independent method) showed that the abundance of fungi in the GT02 sample ((9.43 ± 0.12) × 10 6 copies/g) was approximately seven orders of magnitude higher than that in the GT01 sample ((1.33 ± 0.04) × 10 6 copies/g). This study highlights the mechanisms underlying Moutai flavor development and could be used to further optimize liquor synthesis.